Growth Analysis of Chir (Pinus roxburghii, Sargent) Plantations in Supkhar of Balaghat Division of Madhya Pradesh - Suri, S. K. (Indian Forester, 1984)
Out side its natural habitat, successful Chir pine plantations were raised in the beginning of the twentieth century in Balaghat Division of Madhya Pradesh with a view to provide a nurse crop to the Sal seedlings in grassy blanks. The growth and yield data of the sample plots laid out in these plantations in 1924 have been analysed and studied. The data analysis shows that the site quality conforms to All India Chir Q. I/II; the total volume production per hectare varies from four to two times of the yield table figures; it is a fast growing species; and its rotation of maximnm volume production is around 40 years, It is suggested that grassy blanks in Sal forests in frosty localities may be planted with Chir seeds of Supkhar origin to increase the productivity of forests and a status of provenance be accorded to Supkhar Chir as it has tropicalised in this locality.